Satellite Sound Broadcasting Around 1 GHz - Miller, J. (IEEE journal on selected areas in communications, 1985)
This paper presents the technical factors affecting the design of a geostationary satellite sound broadcasting system operating around 1 GHz to serve low-cost consumer-quality portable and automobile receivers. The technical characteristics for such a system are under study in a number of countries in preparation for the 1985/1988 ITU Space Services Planning Conference.The first session will make appropriate recommendations to the second session on the future regulatory provisions for the service. A medium-quality monophonic or stereophonic service would be provided using frequency modulation. Signals would be received using a simple circularly polarized omnidirectional antenna. Link margins to serve indoor portable receivers and automobile receivers in rural and urban areas are discussed. Building penetration loss for single family dwellings is expected to be about 11.8 dB in 90 percent of the houses not using foil-backed insulation or shadowed by trees, increasing to over 17 dB with foil-backed insulation. Shadowing by trees increases the loss by 12-15 dB. Apartment and commercial building penetration loss is expected to approach 20 dB. Automobile reception in rural areas will be primarily affected by foliage attenuation due to trees. At a 30° elevation angle, an attenuation of about 15 dB with probability of 0.90 is expected. In situations where the line-of-sight path is unobstructed, multipath fading of 2.8 dB at 0.90 probability is the predominant source of degradation. Automobile reception in urban areas requires operating margins of 24-30 dB because of shadowing and multipath by large buildings. Based on the foregoing considerations, an e.i.r.p. from 66 to 79 dBW is required from a geostationary satellite to serve low-cost portable and automobile receivers in rural and urban environments.